The State of Theory in International Politics - SHEMBESH, Dr. ALI (Dirasat in Economics and Business, 1982)
This article discusses and examines the existence of a theory and/or theories of international politics. The discussion starts by defining the term theory and indicating the need for a theory. Furthermore, it Will state if there is a lack of such a theory. However, in the beginning I would rather mention the relationship between approach' and theory. With regard to the relationship between approach and theory in international politics one of the leading scholars in field has contended: "An approach to analysis is not a theory in any of the ordinary senses of that term. Epistemologically, however, approaches are antecedent to theory. That is, it is impossible to construct theoretical statements without employing an approach to analysis either explicitly or implicitly."